El proceso de generación de políticas públicas en la Comunidad Andina. Una propuesta basada en cuatro modelos - Cárdenas Vargas, Diego Fernando (Pontificia Universidad Católica del Perú, 2025)
Latin American scholars, who have studied the Andean subregional integration process, viewed the Andean Community as a less effective attempt to follow the European Union model and pointed to its diffuse institutional framework and the divergent political vision of the Andean countries as deficiencies. However, European scholars, who have addressed their regional integration process, and even compared it with the Andean one, started from a different theoretical notion by cataloging them as supranational political systems, which allowed them, unlike the Latin American scholars, to introduce theoretical and methodological tools of Political Science to understand the policy-making process in the European Union.In this sense, the research article seeks to understand the policy-making process in the Andean Community, incorporating theories, approaches and methodologies of International Relations and Political Science to understand the particularity of Andean policies. In this sense, four modes of policy-making are proposed, categorized as “intergovernmental-political”, characterized by the role of the Andean Presidential Council in defining Andean subregional integration policy and in putting certain issues on the agenda; “intergovernmental-regulatory”, characterized by the guiding role that CAMRE and the Commission play in the design and adoption of policies; “intergovernmental-technical”, characterized by the role that the General Secretariat of the Andean Community plays in the design and adoption of policies; and “multilateral-autonomous”, characterized by the differentiated path taken by certain institutions of the Andean Integration System that develop their own policies with the participation of more Member Countries.

Estudiosos latinoamericanos, que han abordado el proceso de integración subregional andino, entendieron a la Comunidad Andina como un intento de menor efectividad al modelo de la Unión Europea y señalaron como deficiencias su institucionalidad difusa y la divergente visión política de los países andinos que lo conforman. Sin embargo, estudiosos europeos, que han abordado su proceso de integración regional, e incluso comparándolo con el andino, partieron de una noción teórica distinta al catalogarlos como sistemas políticos de carácter supranacional, razón que les permitió, a diferencia de los estudiosos latinoamericanos, introducir herramientas teóricas y metodológicas propias de la Ciencia Política para entender el proceso de generación de políticas públicas europeas. En ese sentido, el artículo de investigación busca comprender el proceso de generación de políticas públicas en la Comunidad Andina, incorporando teorías, enfoques y metodologías de las Relaciones Internacionales y la Ciencia Política que permita entender la particularidad de las políticas públicas andinas. En ese sentido, se proponen cuatro modelos de generación de políticas públicas catalogados como «intergubernamental-político», caracterizado por el rol del Consejo Presidencial Andino en la definición de la política de integración subregional andina y en la puesta en agenda de ciertos temas; «intergubernamental-regulatorio», caracterizado por el rol directriz que el CAMRE y la Comisión manejan en el diseño y adopción de las políticas públicas; «intergubernamental-técnico», caracterizado por el rol que la Secretaría General de la Comunidad Andina maneja en el diseño y adopción de las políticas públicas; y «multilateral-autónomo», caracterizado por el camino diferenciado que han tenido ciertas instituciones del Sistema Andino de Integración que desarrollan sus propias políticas públicas con la participación de más países miembros.
The policy-making process in the Andean Community. A proposal based on four policy modes
Keywords: Policy-making process; Andean Community; Public Policy; Policy modes; Supranationality; Proceso de generación de políticas públicas; Comunidad Andina; Políticas públicas; Modelos; Supranacionalidad; https://purl.org/pe-repo/ocde/ford#5.09.01